Surface Plasmon Resonance (SPR) Phenomenon of the Oxidizing and Reducing Polypyrrole - Nurlaila Rajabiah (Universitas Muhammadiyah Metro, 2016)
Surface Plasmon Resonance (SPR) phenomenon of the oxidizing and reducing polypyrrole (PPy) have been observed using a modified Au/PPy Kretschmann configuration. The observation was carried out through simulation Winspall 3.02 software and compared with some experimental data refractive index (n), absorbance index (), and thickness (τ) reported in other literatures with spectroscopy ellipsometry. This simulation assumed that the SPR system use BK-7 halfcylinder prism (n= 1,515) and the laser beam was generated by HeNe (λ= 632,8 nm). The result showed that the optimum layer thickness of polypyrrole with neutral electrolyte solution in the reduction state is of about 20 nm. The polypyrrole with an acid solution in the oxidation state showed that the reflectivity curve is sharper and the width of the curve is smaller than the neutral electrolyte solution in the reduction state with the SPR angle of about 46,810 and the reflectivity value of about 0,217. Polypyrrole in a state of oxidation and reduction, related to the absorption, film thickness, and dielectric constant of materials, affected to the SPR angle shift and dip curve